Party system renewal or business as usual? Continuity and change in post-bailout Portugal - Lisi, M.; Sanches, E.; Maia, J. S. (South European Society and Politics, 2020)
The recent economic crisis has created momentum for party system change in most European democracies. While Portugal has shown more predictable patterns of interparty competition, since the 2015 elections it has experienced incremental changes in the electoral, parliamentary and governing arenas. This study explores several dimensions of the Portuguese party system (including volatility, alternation in government and innovation) from a longitudinal perspective, and provides new explanations for its development. Focusing on the post-bailout period, it argues that abstention and party strategy go a long way to explaining the patterns of continuity and (marginal) change in the Portuguese party system.